PERAN MEDIASI DIGITAL MARKETING TERHADAP PERILAKU KONSUMEN - Soemarjono, Eko; Tapaningsih, Weni Indah Doktri Agus; Arifin, Samsul (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
KFC Jember Outlet has decreasing on sale of food product in KFC Jember Outlet. An operational manajer KFC Jember Outlet must have smart thinking to increasing sale with customer satisfaction achievement. This research aim to know the role of digital marketing (DM) to mediate price (P) and taste (T) effect on repushase food in KFC Jember Outlet through customer satisfaction (CS). This research use quantitative associative research. This research use simple random sampling technique. This research conducted 730 responden to be a sample. An aanlysis of this research are Structural Equation Model (SEM) with Amos 24 version. Based on this research result, digital marketing (DM) have mediaton role of price (P) and taste (T) effect on repurchase food in KFC Jember Outlet through customer satisfaction